The informative value of adenosine deaminase isoenzymes testing in the diagnosis of tuberculous pleurisy with the relevance to the age of patients - M. E. Dyakova; T. L. Perova; D. S. Esmedlyaeva; P. K. Yablonskiy (Туберкулез и болезни лёгких)
The objective of the study: to assess the diagnostic informative value of ADA isoenzymes – ADA-1 and ADA-2 – in the pleural fluid in case of tuberculous pleurisy with the relevance to the age of patients.Subjects and methods. In 200 patients with pleural effusion of tuberculous etiology and 152 patients with pleural effusion of non-tuberculous etiology, the activity of ADA (and its isoenzymes of ADA-1 and ADA-2) was tested.Results. In patients with tuberculous pleurisy, the activity of ADA, ADA-1 and ADA-2 was significantly higher than in patients with pleurisy of a different etiology. Tests of ADA activity (above the threshold value of 30 u/L) had sensitivity and specificity of 95 and 94%, respectively. The sensitivity of testing the activity of ADA-1 and ADA-2 (above the threshold value of 20 u/L) was 30 and 93% with the specificity of 96% and 88%, respectively. The frequency of detecting the activity of ADA and ADA-2 above the threshold did not depend on the cellular nature of tuberculous pleurisy. The activity of ADA-2 was associated with the percentage of pleural fluid lymphocytes in the case of tuberculosis.No influence of age on the diagnostic informative value of ADA and ADA-2 was found out. ADA-1 activity was weakly positively correlated with the age of the patients.